Povaha ľudskej spolupráce a význam altruistického trestania: Ako sa ľudia správajú v laboratóriu a v teréne? - Martin Hulín (AntropoWebzin, 2014)
There is an increasing interest of behavioral economists in the last decades in studying the nature of human cooperation and morality. Several economic games of social dilemmas have been developed to this end. Based on the results of these games, important conclusions are made about human cooperation. Since people in these games all over the world do not behave completely selfishly and give away money, it is taken as demonstrating other important motivations. When people are given the opportunity to punish free-riders, this increases cooperation, which is again interpreted in the sense of altruistic punishment (strong reciprocity) that is considered a key factor in sustaining cooperation. However, these results are in contrast with the anthropological literature on hunter-gatherers’ cooperation, which highlights other important factors sustaining cooperation, such as the possibility to choose partners, and symbolic and coalitional sanctions (weak reciprocity). The aim of the research is to critically analyze these contrasts and illustrate some aspects of cooperation (conflict resolution, dealing with cheaters, and the role of reputation) from the author’s own research of mutual aid among peasants in Serbia.